2009
DOI: 10.1039/b819809h
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline Langmuir–Blodgett films: formation and properties

Abstract: The deposition and characterisation of Langmuir-Blodgett (LB) layers of polyaniline (PAN) on solid supports is described. Langmuir films were spread as a mixture of PAN and dodecylbenzenesulfonic acid (DBSA) at the water/air interface and deposited on either glass or indium tin oxide (ITO). Mono- and multi-layer films of PAN/DBSA were characterized by X-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM), absorption spectroscopy and cyclic voltammetry (CV). The ultrathin films produced were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 69 publications
2
35
1
Order By: Relevance
“…It has been also reported that the large amphiphilic dopant causes a large increase of the repeat unit area, although formation of ordered polymer films has been shown. 44,45 The solubility of SDS in water affects the surface pressure values, which contributes possibly to the increase of the repeat unit area obtained in this study.…”
Section: Resultsmentioning
confidence: 93%
“…It has been also reported that the large amphiphilic dopant causes a large increase of the repeat unit area, although formation of ordered polymer films has been shown. 44,45 The solubility of SDS in water affects the surface pressure values, which contributes possibly to the increase of the repeat unit area obtained in this study.…”
Section: Resultsmentioning
confidence: 93%
“…For example, it is well-known that an expanded-coil conformation of doped PANI molecules leads to increased infrared absorption in the electronic spectrum, it also improves mechanical properties and increases electrical conductivity of the film as compared with the film where the molecules are in the compact-coil conformation [1]. In order to provide a required structural organization of a polymer film, various deposition techniques can be employed, such as chemical and electrochemical deposition onto specific substrates [2], spin-and drop-casting [3,4], Langmuir-Blodgett [5][6][7], self-assembly [8][9][10], grafting to the surface [11,12], and molecular imprinting [13]. While many techniques provide more or less controlled structure of PANI films, casting from a solution still leads to ambiguous results in respect to the film structure, since the nature of a cast film depends critically on the relative rate of solvent evaporation in respect to the rate at which changes in molecular interaction occur.…”
Section: Introductionmentioning
confidence: 99%
“…Depth analysis by XPS can provide such information and has successfully been performed for polymeric materials. Zhang et al 40 conducted an XPS analysis of multilayered PANI films measured at different take off angles (90° and 15°). 38 Gilbert et al, 39 investigated the multilayers of polyelectrolytes and revealed the inter layer diffusivity of chitosan in [poly(acrylic acid)/poly(ethylene oxide)] (PAA/PEO) films.…”
Section: Introductionmentioning
confidence: 99%